Effects of early weaning on performance of cow/calf pairs - E.A. Koch; J.A. Christopher; T.T. Marston; Ryan M. Breiner; John A. Unruh (Kansas Agricultural Experiment Station Research Reports, 2004)
Commercial cow/calf pairs (Angus based, n=103) were used to determine the effect of calf weaning age on cow body weight and body condition score (scale=1 to 9) and calf performance in terms of subcutaneous fat and marbling deposition. Only cows with male progeny (steers, n=52; bulls, n=51) were used in this study. Treatments were: 1) early-weaned bulls, 2) early-weaned steers, 3) traditionally weaned bulls, and 4) traditionally weaned steers. Cow/calf pairs grazed pastures at four different locations. Calving began February 1, 2003, and ended in early April. In the early-weaned treatment group, calves were weaned June 25, with an average age of 115 days. In the late-weaned treatment group, calves were weaned October 6, with an average age of 218 days. The data indicate that the cows in the early-weaned treatment group gained 121 lb more weight (P<0.0001), had 0.13 inches more external backfat (P<0.0001), and had an average body condition score 1.2 greater (P<.0001) than their late-weaned counterparts. All steer calves were implanted before they entered the feedlot. Early weaning and subsequent feedlot placement produced heavier calves at approximately nine months of age. Ultrasound technology indicated that early-weaned calves had greater backfat and marbling scores 26 days after feedlot placement than did traditionally weaned calves. However, the early-weaned bulls had less backfat at a similar average weight to their steer contemporaries.
Keywords: Cattlemen& #x27; s Day; 2004; Kansas Agricultural Experiment Station contribution; no. 04-242-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 923; Beef; Early weaning; Cow/calf pairs